Boosting Cu(In, Ga)Se2 Thin Film Growth in Low-Temperature Rapid-Deposition Processes: An Improved Design for the Single-Heating Knudsen Effusion Cell. (April 2021) - Zhang, Yunxiang; Lin, Shuping; Cheng, Shiqing; He, Zhichao; Hu, Zhaojing; Zhou, Zhiqiang; Liu, Wei; Sun, Yun
Highlights: Incomplete metal selenides is observed in Cu(In, Ga)Se2 films, particularly for a low-temperature rapid-deposition process. A new single-heating Knudsen effusion is designed to improve the quality of CIGS film. The performance of Cu(In, Ga)Se2 solar cell grown in low-temperature rapid-deposition processes has been improved obviously. Abstract: The Knudsen effusion cell is often used to grow high-quality Cu(In, Ga)Se2 (CIGS) thin film in co-evaporation processes. However, the traditional single-heating Knudsen effusion cell cannot deliver complete metal selenides during the whole deposition process, particularly for a low-temperature deposition process, which is probably due to the condensation and droplet ejection at the nozzle of the crucible. In this study, thermodynamics analysis is conducted to decipher the reason for this phenomenon. Furthermore, a new single-heating Knudsen effusion is proposed to solve this difficult problem, which leads to an improvement in the quality of CIGS film and a relative increase in conversion efficiency of 29% at a growth rate of about 230 nm·min −1, compared with the traditional efficiency in a low-temperature rapid-deposition process.